Cullin 1 is not associated with late-onset preeclampsia - Samara, Tjam Diana; Liem, Isabella Kurnia; Prijanti, Ani Retno; Andrijono, Andrijono (Faculty of Medicine, Trisakti University, 2019)
BackgroundLate-onset preeclampsia (PE) is preeclampsia occurring after 34 weeks of gestational age or later. Cullin 1 (CUL1), a proangiogenic protein, is expressed in the placenta, where an imbalance between proangiogenic and antiangiogenic proteins during gestation can cause disturbance of trophoblast invasion. This defect results in vascular ischemia that may produce preeclampsia. The objective of this study was to determine the correlation between CUL1 as proangiogenic factor and late-onset preeclampsia. MethodsThis study was of analytical observational cross-sectional design and involved 44 preeclampsia patients with ³34 weeks of gestational age (late-onset PE). The CUL1 level in the subjects’ sera, taken before they gave birth, and in homogenates of their placenta, obtained per vaginam or by cesarean section, were examined by the ELISA technique. Statistical analysis was performed with the Spearman correlation test with significant p value of <0.05.ResultsMedian maternal age was 31 years and median gestational age was 37 weeks. Median serum CUL1 was 41.78 pg/mL and median placental homogenate CUL1 was 32.24 pg per milligram of total placental tissue protein. There was no significant correlation between serum CUL1 level and late-onset preeclampsia (r=-0.281; p=0.065). There was also no significant correlation between placental CUL1 level and late-onset preeclampsia (r=-0.166; p=0.281).ConclusionSerum CUL1 and placental CUL1 were not correlated with late-onset preeclampsia. However, this study indicated that low serum CUL1 tends to prolong gestational age in preeclampsia.